(untitled) (Heritage, 2022)
With the development of new technologies, the logical question is what will libraries look like in the future, will they have physical space? What is certain is that libraries will remain centers of knowledge and information, only that in the future printed books will be slowly replaced by electric readers and electronic books. One of the roles of public libraries in the 21st century is to be the bearers of the digitalization of heritage culture, which will make it available to everyone electronically. Creating new ways for users to access knowledge is an effective response to the challenges that this sector will face in the near future. This changes the way of communication with users. One of the ways to actively communicate with users is the "Ask a Librarian" service. Communication between librarians and users is key to designing and implementing new types of services and knowledge.